PERAN AUDIT DALAM TATA KELOLA PERUSAHAAN: STUDI KASUS PADA PT INDUSTRI JAMU DAN FARMASI SIDO MUNCUL TBK. - Vero, M. Adnan; Miharja, Kasmanto; Rizqi, M. Awwallu; Ramadhan, Fikri (Universitas Trilogi, 2024)
The research aims to analyze the role of audit in corporate governance of PT Industri Jamu and Farmasi Sido Muncul Tbk by using observation methods and related literature study methods. The results of the research above state that internal and external audits provide accountability reports and verify that financial reports are in accordance with generally accepted accounting principles and international financial reporting standards to ensure that financial reports provide a fair and correct picture of the company's financial condition.Keywords: Audit; Internal Audit; External Audit; Corporate Governance